Prarancangan Pabrik Biodiesel Dari Minyak Biji Nyamplung Dengan Proses Esterifikasi-Transesterifikasi Kapasitas 15.000 Ton/Tahun - HIDAYATI, SRI; , Kusmiyati, S.T, M.T, Ph.D; , Dr. Ir. Ahmad M. Fuadi, M.T (2015)
Biodiesel is one type of alternative diesel fuel made from natural materials. Biodiesel needs will continue to grow in line with the policy of the use of biodiesel as a fuel oil additive. Biodiesel refers to the quality standards ISO 7182: 2012 and the decision EBTKE No. 723 K / 10 / DJE / 2013. This plant with a capacity of 15,000 tonnes per year are planned to be established in East Kalimantan Balikpapan Subdistrict Kariangau precisely in the West that operate for 330 days per year. Biodiesel from oil seeds nyamplung reacted through esterification process - transesterification performed in a stirred tank reactor Flow (RATB) with methanol reactants and catalysts H2SO4 and NaOH at a pressure of 1 atm, a temperature of 60 ° C. This process runs on liquid-liquid phase, reversible, exothermic and isothermal. Nyamplung seed oil demand for this plant as much 1893.9394 kg / h, and methanol as much 378.7879 kg / hour. Products in the form of biodiesel as 1749.3826 kg / hour. In the utility unit, needs water to process water as much as 874.6913 kg / hour of Reservoir Wain East Kalimantan. Whereas the steam takes steam generating unit 74.70 kg / hr, pneumatic control equipment needs about 3.09 kmol / h. For the power generation part of the process as much as 26.5965 Kw obtained from PT PLN and generator sets. The results of the economic analysis of plant production capacity of 15,000 tons per year is the result of average annual sales of Rp. 305,759,650,970.4000. The profit before taxes of Rp. 52,018,646,492.6500 and profit after tax of 30% to Rp. 36,413,052,544.8550. Average production costs per Rp. 6.973.255.273.292,14.Pay Out Time (POT) before tax for 4.8 years and 4.7 years after tax for, Rate Of Return Investments (ROI) before tax of 16.0626% and after tax amounted to 11, 2438%, Break Even Point (BEP) of 56.0639%. Shut Down Point (SDP) of 23.2403%. Age mill for 10 years and Discounted Cash Flow Rate (DCFR) amounted to 37.9%. In terms of simple process and economic evaluation of the data calculations meet the standards, then this plant deserves established.